PENGARUH MOTIVASI KERJA TERHADAP KEPUASAN KERJA GURU SMA YADIKA SE-JABODETABEK - Edi Siregar (Jurnal Satya Mandiri Manajemen dan Bisnis, 2015)
The objective of this research is to assess the effects of teachers’ work motivation on their work satisfaction. The causal study was conducted in YADIKA high schools at Jabodetabek, from January to March 2015, involving a sample of 60 teachers, who had been selected from all the teachers of schools by using the proportional random sampling technique. A survey was applied in this research and the data were analysed with technique by putting variables in a correlation matrix. The results of research reveal direct effects of the work motivation on the work satisfaction. This implies the need to consider the teachers’ work motivation in the strategic plan of YADIKA high schools at Jabodetabek to improve the teachers’ work satisfaction.